Analysis of lard in sausage using Fourier transform infrared spectrophotometer combined with chemometrics - Any Guntarti; Mustafa Ahda; Aprilia Kusbandari; Satriyo W Prihandoko (Wolters Kluwer Medknow Publications, 2019)
Sausage is one of foods which must be confirmed halal to consumers. Meat is commonly used in producing sausages, especially beef. However, due to high cost of meat producer usually mixes the ingredients with other cheaper meats, such as pork. This study aimed to analyze the differences in the spectral profile of lard and beef in the sausages using Fourier transform infrared (FTIR). Lard and beef tallow was extracted using Soxhlet apparatus at ±70°C for 6 h with n-hexane. After extraction, lard and beef tallow was evaporated. Then obtained fats were stored in eppendorf and analyzed using FTIR spectrophotometer. The results were then combined with chemometrics such as Partial least squares (PLS) for the quantitative analysis and principal component analysis (PCA) for classification. PLS and PCA analysis was performed on 1200-1000 cm-1. The results of the analyzed PLS provided the linear regression equation y = 0.921x + 4.623 with R2 = 0.985 and root-mean-square error of calibration (RMSEC) = 2.094%. External validation root-mean-square error of prediction (RMSEP) was 4.77% and internal validation root-mean-square-error cross-validation (RMSECV) was 5.12%. The results of the PCA analysis showed the classification of different quadrants between 100% pork sausage and 100% beef sausage. Thus, it can be concluded that FTIR spectroscopy method combined with chemometrics can be applied to identify the presence of pork in the sausage.